Determinants of Transaction Ease Among Users of the DANA Platform as a Payment Method: A Study on FEBI Students at IAIN Bone - Widya; Jumarni; Rahma Hidayati Darwis (Penerbit Jurnal Indonesia, 2025)
This research analyzes the determinants of transaction convenience for DANA platform users among FEBI IAIN Bone students. Using a quantitative method, the study examines the influence of three independent variables—security, service features, and digital financial literacy—on transaction convenience as the dependent variable. Data was collected through questionnaires distributed to 100 respondents selected using purposive sampling and analyzed using SmartPLS 4. The results demonstrate that all three independent variables significantly influence transaction convenience on the DANA platform. Transaction security, provided service features, and users' digital financial literacy levels prove to have important roles in enhancing the platform's ease of use. The study recommends that service providers continue to improve security aspects, develop intuitive features, and provide digital financial literacy education to users to create a more comfortable, secure, and efficient transaction experience. The findings encourage digital wallet providers to focus on these three key factors to enhance user experience, making transactions more convenient and efficient for their customers.